{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

2c03-review - 00065

2c03-review - 00065 - Hence T(n,m(C(0,k C(1,k C(i,k C(k,k...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
8 Hence: T(n,m) (C(0,k)+C(1,k)+. ..+C(i,k)+. ..+C(k,k)) c + (2 k+1 -1)c = 2 k c + (2 k+1 -1)c = (3·2 k – 1)c = (3·2 n/2 – 1)c = O(2 n/2 ). One also may suspect O(2 n/2 ) solution, and prove it by induction. c. we use the recursive formulation, to fill entries of the table like the example shown below: for example for m=3, n=7 0 1 2 3 0 1 1 1 1 2 1 2 1 3 1 3 3 1 4 1 4 6 4 5 1 5 10 10 6 1 6 15 20 7 1 7 21 35 We fill the table using this formulation: 1 (, ) 1 0 (1 , )(1 , 1 ) ij li j j l i j l i j others = == −+ d.
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

Ask a homework question - tutors are online